2017
DOI: 10.1038/s41467-017-00770-7
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil polarization by IL-27 as a therapeutic target for intracerebral hemorrhage

Abstract: Shortly after intracerebral hemorrhage, neutrophils infiltrate the intracerebral hemorrhage-injured brain. Once within the brain, neutrophils degranulate, releasing destructive molecules that may exacerbate brain damage. However, neutrophils also release beneficial molecules, including iron-scavenging lactoferrin that may limit hematoma/iron-mediated brain injury after intracerebral hemorrhage. Here, we show that the immunoregulatory cytokine interleukin-27 is upregulated centrally and peripherally after intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 64 publications
3
134
0
Order By: Relevance
“…Shortly after ICH, neutrophils infiltrate into the hemorrhagic brain and contribute to the secondary brain injury by releasing pro‐inflammatory factors, reactive oxygen species, proteases, and matrix metalloproteinases . Recently, neutrophils were reported to have a beneficial effect in a rodent blood‐induced ICH model . In the ischemic brain, infiltrating neutrophils show a pro‐inflammatory N1 phenotype or an anti‐inflammatory N2 phenotype .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shortly after ICH, neutrophils infiltrate into the hemorrhagic brain and contribute to the secondary brain injury by releasing pro‐inflammatory factors, reactive oxygen species, proteases, and matrix metalloproteinases . Recently, neutrophils were reported to have a beneficial effect in a rodent blood‐induced ICH model . In the ischemic brain, infiltrating neutrophils show a pro‐inflammatory N1 phenotype or an anti‐inflammatory N2 phenotype .…”
Section: Discussionmentioning
confidence: 99%
“…19 In the ischemic brain, infiltrating neutrophils show a pro-inflammatory N1 phenotype or an anti-inflammatory N2 phenotype. 46,58 Although previous studies have revealed that neutrophils infiltrate the hemorrhagic brain of animal models and undergo polarization, 19,64 to our knowledge there are no reports of neutrophil phenotype in ICH patients. CD45 + CD11b + Ly6G high and CD45 + CD11b + Ly6G low have been used to stratify the population of neutrophils in animals.…”
Section: F I G U R E 4 Influence Of Time From Symptom Onset To Mis Lmentioning
confidence: 99%
See 1 more Smart Citation
“…This population displays neuroprotective features, limits inflammation and promotes resolution . Alternative neutrophil subsets with iron‐scavenging and neuroprotective properties during intracerebral haemorrhage have also been reported . Thus, neutrophils perform dual roles in the progression of ischaemic brain injury: during the early stages, they drive inflammation, and at later stages, they promote resolution.…”
Section: Vascular Inflammation and Diseasementioning
confidence: 99%
“…88 Alternative neutrophil subsets with iron-scavenging and neuroprotective properties during intracerebral haemorrhage have also been reported. 89 Thus, neutrophils perform dual roles in the progression of ischaemic brain injury: during the early stages, they drive inflammation, and at later stages, they promote resolution. This duality suggests that targeting bulk neutrophil infiltration into the ischaemic core may not be an optimal strategy towards the treatment of stroke.…”
Section: Ischaemia-reperfusion Injurymentioning
confidence: 99%